AUT-CPT & Pile Database for Piling Performance Using CPT and CPTU Records - Sara Moshfeghi; Abolfazl Eslami; Seyyed Majdeddin Mir Mohammad Hosseini (Deep Foundations Institute, 2017)
"Due to variety of current pile bearing capacity methods based on the cone penetration test (CPT), for optimum design, it is necessary to evaluate the performance of such methods in different geotechnical conditions. Geotechnical databases including piling and in-situ testing records have been recognized as useful tools for analysis, design and economical construction. In order to evaluate pile bearing capacity methods, AUT-CPT&Pile database has been compiled including 450 full scale pile load tests and CPT sounding records. This database consists of different pile types with a relatively wide range of geometries and various soil conditions. Forty three records of piles driven in sand deposits were then employed to evaluate effects of ultimate capacity interpretation criteria from load displacement diagrams. The Davisson offset limit criterion, the Brinch Hansen 80% criterion and the load at the displacement of 10% of the pile diameter were compared to estimated capacities from ten CPT based design methods currently used in practice. The Brinch Hansen 80% criterion and the load at the displacement of 10% of the pile diameter lead to reasonable results, the Brinch Hansen 80% criterion showed less scatter. For evaluating the accuracy and the precision of CPT-based methods, the results were compared to estimated capacities. Results of comparison indicate that the CPT-based methods mainly predict the pile capacity withreasonable accuracy.INTRODUCTIONAmong the different approaches of estimating the pile bearing capacity, in-situ tests, especially, the cone penetration test (CPT) are favored due to the cone similarities with piles in modes of installation as well as fast and continuous profiling. This trend is practically well established where deep foundations are to be constructed in soft to medium subsoil deposits (Eslami and Fellenius, 1997; Mayne and Niazi, 2009).Employing different design methods results in a wide range of values which complicates the selection of an appropriate one to determine the pile bearing capacity. Several studies by Briuad and Tucker (1988), Eslami and Fellenius (1997), Abu Farsakh and Titi (2004), Schneider et al. (2008) and Eslami et al. (2011) confirm disparity of different design methods predictions. Thus, for optimum design, it is necessary to evaluate and compare the performance of current methods.Geotechnical databases are known as helpful tools in research and practical applications for optimizing analysis and design and are mainly used for management and interpretation of data, evaluation of design methods, calibrating LRFD or ASD design factors, etc. Pile lateral and axial load tests are examples of databases in geotechnical engineering. A summary of several CPT and pile load test databases is presented in Table 1."